Life cycle assessment of end-of-life options for two biodegradable packaging materials: sound application of the European waste hierarchy. (1st January 2015) - Rossi, Vincent; Cleeve-Edwards, Nina; Lundquist, Lars; Schenker, Urs; Dubois, Carole; Humbert, Sebastien; Jolliet, Olivier
Abstract: The purpose of this study is to assess whether for dry biodegradable packaging without food contamination, a detailed life cycle assessment supports the priorities suggested by the five-level hierarchy, as described by the European Waste Directive 2006/12/EC. Environmental impacts and water withdrawal were assessed using an extended version of IMPACT 2002+, accounting for the dynamic pattern of greenhouse gas releases for each scenario when determining Global Warming Potentials for a time horizon of 100 years (in this paper defined as dynamic assessment). The present assessment shows that, for most impact categories, mechanical recycling is the most interesting option, followed by direct fuel substitution. Intermediate performances are obtained by anaerobic digestion and municipal incineration. Landfill and industrial composting of dry packaging generate the highest environmental impacts of the studied end-of-life options. Indeed, the composting of the studied materials does not substantially improve compost quality and does not enable energy recovery. The hypothesis that composting is by default environmentally preferable over energy recovery because it is a form of recycling is not confirmed by the present study, thus underlining the importance of a sound and case-specific application of the EU waste hierarchy and the need to complete the hierarchy by product specific studies. Though of limited effect on the present study, the dynamic assessment of greenhouse gas may moderately decrease the impacts effectively taking place over the 100-year horizon. More important is to consider the degradation patterns of biodegradable materials and present to the decision makers both the 100-year and the long term impacts of the end-of-life options. Highlights: The application of the EU waste hierarchy is tested for dry biodegradable packaging. Environmental benefit of plastic composting is low compared to other treatments. The hierarchy should differentiate valuable mechanical from low benefit recycling. It is important to check the EU waste hierarchy against product-specific studies. Decision makers should consider both 100-year and long term climate impacts.